Identification of potential aquaculture sites in solar saltscapes via the Analytic Hierarchy Process - Teixeira, Zara (2018)
The European Commission has identified competition for space as one of the main factors contributing to the stagnation of EU aquaculture production and has recommended coordinated spatial planning, as a mean to identify sites with favorable operational characteristics for aquaculture and lower potential for conflict with other activities. In coastal areas of the Mediterranean, pond aquaculture has emerged as an alternative to salt production in abandoned artisanal Salinas, compromising the delivery of Ecosystem Services in wetland areas. To establish a methodology to estimate the physical carrying capacity for coastal pond aquaculture, and the contribution of the ecosystem to the value of provisioning services from aquaculture, while minimizing the competition for space with solar salt production, we applied a multicriteria-decision making tool (AHP method) to identify priority areas for extensive and semi-intensive aquaculture development in solar saltscapes, taking into account physical factors of ecological and social nature. The study presents spatial allocation scenarios for aquaculture development in the saltscapes of the Figueira da Foz, in the Atlantic coastal zone of Portugal. The physical carrying capacity for the two scenarios presented indicates a potential increase of the area occupied by aquaculture farms in ponds previously occupied by inactive farms and flooded/land filled salterns, whose sites tend to minimize conflict with salt production through avoiding the same water input location and being adjacent to active farms. In conclusion, the approach applied has proven to be successful to manage space competition between aquaculture and salt production, contributing to a sustainable increase of the value of the provisioning of ecosystem services from aquaculture. In future studies, estimation of the social carrying capacity should be combined with the approach followed in this study to improve the definition of the acceptable social limits for aquaculture development in saltscapes.